Passive Leg Elevation to Prevent Newborn Low APGAR and Hypotension of Mothers Undergoing a Spinal Anesthesia for Elective Caesarean Section - Mitra Jabalameli; Shahnaz Aram; Ibrahim Jomee (مجله دانشکده پزشکی اصفهان, 2014)
Background: Hypotension occurs significantly during cesarean operation with spinal anesthesia. This side-effect can be harmful to the mother and the fetus. In this study, impact of passive leg elevation maneuver on prevention of mother hypotension and newborn APGAR index was examined.